Effects of Coating with Different Doses of Boron Compound on Germination Parameters of Cotton Seeds - Mustafa Yaşar; Nurettin Baran; Yusuf Güzel Demiray; Remzi Ekinci; Yaşar Karadağ (Turkish Journal of Agriculture: Food Science and Technology)
In this study, seeds of cotton plants were coated with different boron concentrations and their effect on seedling growth was investigated. The experiment was carried out at Muş Alparslan University, Faculty of Applied Sciences, Department of Plant Production and Technologies, under laboratory and greenhouse conditions, according to the Randomized Plots Trial Design with 4 in laboratory and 3  in greenhouse replications, respectively. In the study, Di-sodium tetraborate decahydrate (Na2B4O7.10H20) (M=381.37 g mol-1)  with a minimum purity of 99% boron compound have been used in different doses; 0 (control), 250, 500, 750, 1000, 1250, 1500, 1750, 2000, 2250 and 2500 mg kg-1. According to the results of the regression analysis, it was determined that as the boron dose in the application increased, the root length was positively correlated and other parameters were negatively correlated. In terms of the parameters examined, 250 mg kg-1 Kaolin+liquid K-Humate (15% HA) 400 ml kg-1 (U3) boron application under laboratory conditions showed better results, and 1000 ml kg-1 Kaolin+liquid boron application under greenhouse conditions. It was determined that the application of K-Humate (15% HA) 400 ml kg-1 (U6) promoted growth. In addition, it was found that the results were confirmed in the grouping of the relationships between applications and parameters with heat map clustering and PCA graphs. As a result, it was determined that the toxic range of boron applications applied to the seed in the cotton plant was very narrow, and that it promoted seedling development and root elongation in the U6 application, but it was concluded that the study should also be studied in field trials in order to make more decisive decisions.